EPID-15. RACIAL AND SOCIOECONOMIC DISPARITIES DIFFERENTIALLY AFFECT OVERALL AND CAUSE-SPECIFIC SURVIVAL IN GLIOBLASTOMA. (9th November 2020) - Liu, Elisa; Yu, Sharon; Sulman, Erik; Kurz, Sylvia
Abstract: BACKGROUND: The prognostic role of racial and socioeconomic factors in patients with glioblastoma is controversially debated. We aimed to evaluate how these factors may affect survival outcomes in an overall and cause-specific manner using large, national cancer registry cohort data in the temozolomide chemoradiation era. METHODS: The National Cancer Institute's Surveillance, Epidemiology, and End Results database was queried for patients diagnosed with glioblastoma between 2005 and 2016. Overall survival was assessed using Cox proportional hazard models using disease intrinsic and extrinsic factors. Cause-specific mortality was assessed using cumulative incidence curves and modeled using multivariate cumulative risk regression. RESULTS: A total of 28, 954 patients met the prespecified inclusion criteria and were included in this analysis. The following factors were associated with all-cause mortality: age, calendar year of diagnosis, sex, treatment receipt, tumor size, tumor location, extent of resection, median household income, and race. Asian/Pacific Islanders and Hispanic Whites had lower mortality compared to Non-Hispanic Whites. Cause-specific mortality was associated with both racial and socioeconomic groups. After adjusting for treatment and tumor-related factors, Asian/Pacific and black patients had lower glioblastoma-specific mortality. However, lower median household income and black race were associated with significantly higher non-glioblastoma mortality. CONCLUSION: Despite the aggressive nature of glioblastoma, racial and socioeconomic factors influence glioblastoma-specific and non-glioblastoma associated mortality. Our study shows that patient race has an impact on glioblastoma-associated mortality independently of tumor and treatment related factors. Importantly, socioeconomic and racial differences largely contribute to non-glioblastoma mortality, including death from other cancers, cardio- and cerebrovascular events.